The Histopathological Spectrum of Pyogenic Granuloma: A Case Series - Vinay Marla; Ashish Shrestha; Khushboo Goel; Sajeev Shrestha (Case Reports in Dentistry)
Background. Pyogenic granuloma is a reactive tumor-like lesion commonly affecting the oral cavity. These lesions usually appear as localized solitary nodule with a sessile or pedunculated base and colour varying from red, purplish, or pink, depending on the vascularity of the lesion. Pyogenic granuloma shows predilection for gingiva and is usually slow growing, but at times it shows rapid growth. The natural course of this lesion can be categorized into three distinct phases, namely, (i) cellular phase, (ii) capillary phase/vascular phase, and (iii) involutionary phase. Histopathologically, pyogenic granuloma is classified into lobular capillary hemangioma (LCH) and non-lobular capillary hemangioma (non-LCH). Case Presentation. In this series, four cases (varied age groups and both genders) of pyogenic granuloma showing varying histopathological presentation in relation to its clinical course have been described. The lesion in its early phase reveals diffuse endothelial cells, with few budding into capillaries. Among the capillary phase, the LCH type shows numerous blood vessels organized into lobular aggregates whereas the non-LCH type does not show any such organization and resembles granulation tissue. The involutionary phase shows healing of the lesion and is characterized by extensive fibrosis in the connective tissue. Conclusion. In conclusion, knowledge of the various histopathological presentation of this lesion is necessary for proper identification.